2015
DOI: 10.1073/pnas.1513509112
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 deficiency protects from type 1 diabetes through the regulation of chemotaxis into the pancreatic islets

Abstract: Studies in animal models and human subjects have shown that both innate and adaptive immunity contribute to the pathogenesis of type 1 diabetes (T1D). Whereas the role of TLR signaling pathways in T1D has been extensively studied, the contribution of the nucleotidebinding oligomerization domain, leucine-rich repeat and pyrin domaincontaining protein (NLRP) 3 inflammasome pathway remains to be explored. In this study, we report that NLRP3 plays an important role in the development of T1D in the nonobese diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 41 publications
3
96
1
3
Order By: Relevance
“…We recently showed that NLRP3 alters T1DM development by limiting the recruitment and infiltration of autoreactive CD4 + T-cells into the pancreas [15]. Our current study provides evidence that NLR signaling is important for modulating diabetes susceptibility by alteration of the microbial composition, which in turn affects the phenotype and functions of immune cells.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…We recently showed that NLRP3 alters T1DM development by limiting the recruitment and infiltration of autoreactive CD4 + T-cells into the pancreas [15]. Our current study provides evidence that NLR signaling is important for modulating diabetes susceptibility by alteration of the microbial composition, which in turn affects the phenotype and functions of immune cells.…”
Section: Discussionsupporting
confidence: 57%
“…However, much less is known about the role of NLR family members in T1DM susceptibility, in humans and mice. We recently reported that NLRP3, an important inflammasome component, influences T1DM development by regulating chemokines and their receptors in both immune cells and islet beta cells, preventing immune cell migration to the targeted tissue [15].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that ablation of Nlrp3 expression in pancreatic islets, comprised of nonhematopoietic cells, can compromise migration of immune cells to pancreatic islets (49). This raises the possibility that nonhematopoietic cochlear cells can also express NLRP3/Nlrp3 and contribute to cochlear autoinflammation in humans with DFNA34 or CAPS.…”
Section: Discussionmentioning
confidence: 99%
“…However, mechanistic studies are currently under investigation. To investigate the role of the inflammasome in the immuno-pathogenesis of T1D development, we developed NLRP3-deficient NOD mice [129]. In the absence of NLRP3, NOD mice developed a reduced incidence of T1D.…”
Section: The Role Of the Gut Microbiota In Modifying Diabetes Suscmentioning
confidence: 99%